PENINGKATAN HASIL BELAJAR FIQIH MELALUI PENDEKATAN SAINTIFIK DI KELAS VIII B PUTRI MADRASAH TSANAWIAH NURUL IMAN ULU GEDONG KECAMATAN DANAU TELUK KOTA JAMBI - Delvi Pradela Utami; Sukarno; Samsu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes in Fiqh among female students of class VIII B at Madrasah Tsanawiyah Ulu Gedong, Danau Teluk District, Jambi City. This is indicated by the students' average learning score, which only reached 65, while the minimum passing grade (KKM) set by the school is 75. Furthermore, the learning process conducted by the teacher still follows a conventional approach with limited variation in methods. This study focuses on the use of the scientific approach in teaching Fiqh, particularly the material on recommended prostrations (sujud-sujud yang disunnahkan). The purpose of this research is to improve students’ Fiqh learning outcomes through the application of the scientific approach in class VIII B.This study is a Classroom Action Research (CAR) conducted at MTs Nurul Iman Ulu Gedong, involving 15 female students as research subjects. The object of this study is the students' learning outcomes. The instruments used include teacher activity observation sheets, student activity observation sheets, interview guidelines, and multiple-choice test questions. Data analysis techniques employed in this study consist of both quantitative and qualitative analysis. The results of the study show that the application of the scientific approach in Fiqh learning made students more active and eliminated boredom, as reflected in their enthusiastic participation. In terms of learning outcomes, the average score in cycle I 76,3 reached 66.67%, while in cycle II, the average score increased 83,2 to 86.67%. Based on these findings, it can be concluded that using the scientific approach can improve students’ learning outcomes. The study suggests that school principals, teachers, and other researchers continue to develop and expand this research to achieve even more optimal results. Keywords: Learning Outcomes, Scientific Approach Bottom of Form